THE DEVELOPMENT OF STUDENT ACTIVITY SHEET (SAS) THROUGH COOPERATIVE LEARNING MODEL TYPE GROUP INVESTIGATION (GI) TO PRACTICE SCIENCE PROCESS SKILL ON MATTER OF ACID BASE FOR CLASS XI (UNESA Journal of Chemical Education, 2018)
This study aims to determine and describe the feasibility of Student Activity Sheet by using cooperative learning with group investigation type to practice the science process skilss on acid base for XI grade in terms of validity, practicality, and effectiveness. The design of this study using Reseach and Develompent (RnD) method proposed by Sugiyono until the limited trial step. A limited trial was conducted to 20 students of class XI SMAN 18 Surabaya. Student activity sheet based on cooperative learning model of type of group investigation to practice the science process on acid-base class XI grade has fulfilled the feasibility of the criteria of validity, practicality and effectiveness so it can be used in teaching and learning process. The validation result which has been obtained from the Student activity sheet is very feasible based on the content and construct validity criteria with the percentage of 86% and 85%, for the criteria of practicality in terms of responses of students who have very responsive category with 97% and supported by student activity which has a percentage of 96.25 %, whereas for the effectiveness of the Student activity sheet based on the test results of the accuracy of knowledge and the existing value of 100% classical completeness and the result n-gain value where the students are in the medium category as much as 20% and the students who are in the high category as much as 80%. Keywords: Student activity sheet,cooperative learning model type group investigation, science process skill, acid base.